Psychophysiology of gymnasts: specifics of sports specialization - Chayun D.V. , (Theory and Practice of Physical Culture, 2025)
Objective of the study was to investigate the psychological and physiological traits of the young athletes from the Tyumen region who participate in cheerleading, gymnastics, and aerobics, aged between 12 and 14, and 15 and 17. Methods and structure of the study. A psychophysiological analysis was conducted on female athletes from the Tyumen region who participate in cheerleading, gymnastics, and aerobics. The assessment of their psychophysiological characteristics was conducted during the 2023-2024 sports season, utilizing the UPFT 1/30 – Psychophysiologist device and the psychomotor test module. Results and conclusions. It was found that the members of the regional cheerleading team tend to have a set of traits associated with a weak nervous system, while the members of the gymnastics team tend to have a medium-weak nervous system, and the members of the aerobics team tend to have a strong nervous system. At the same time, the members of the cheerleading and aerobics teams tend to have a very high level of functional mobility of their nervous processes, while 40% of the gymnastics team members had a low level in this regard. Despite these differences, all the members of the teams share a tendency towards inhibition of nervous processes, which suggests that the members of the Tyumen region national teams in gymnastics are resilient to stress.